Jurnal Sistem Informasi Persediaan Barang Dengan Metode Buffer Stock Berbasis Web - Firnanda, Silma; Aqham, Ahmad Ashifuddin; Sudibyo, Sukemi Kamto; Siswanto, Edy (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Inventory management plays a crucial role in ensuring smooth business operations by preventing stockouts that may cause losses. Toko Cat Gani still relies on manual recording, which is prone to data loss, duplicate entries, and delays in stock reporting, thus requiring a systematic solution. This study aims to design and implement a web-based inventory information system using the buffer stock method to overcome these issues. The research method employed is Research and Development (R&D) with a prototype model, consisting of needs analysis, system design, validation, and testing stages. The system was developed using PHP, MySQL, and XAMPP, featuring item data management, supplier management, inbound and outbound transactions, buffer stock calculations, and real-time inventory reports. The implementation results show that the system facilitates transaction recording, minimizes data entry errors, provides notifications when stock reaches the minimum threshold, and generates accurate and timely reports. Expert validation and user testing confirm that the system is feasible and effective in supporting inventory management at Toko Cat Gani. Therefore, the implementation of a web-based inventory information system with the buffer stock method can be considered an efficient and reliable solution to improve accuracy and effectiveness in inventory control.